The Most Important Factor Influencing Quality of Life Among Cancer-related Psychological Symptoms - Namgi Lee; Byeongkwan Kim (Gonabad University of Medical Sciences, 2024)
Background: Despite progress in cancer treatment, patients often experience pain and emotional distress, which can reduce sleep quality and, ultimately, the quality of life (QoL). This study aimed to identify the most important factors influencing QoL among cancer-related psychological symptoms in patients with cancer.  Methods: This cross-sectional study with a correlational research design recruited 63 participants with cancer diagnoses from a cancer rehabilitation center in South Korea. Data were collected through convenience sampling between October 2023 and February 2024 using the following questionnaires: The European Organization for Research and Treatment of Cancer Core QoL questionnaire (EORTC QLQ-C30), consisting of 15 items to assess QoL and the breakthrough pain assessment tool (BPAT), brief fatigue inventory (BFI), Beck anxiety inventory (BAI), Beck depression inventory (BDI) and Pittsburgh sleep quality index (PSQI) to measure cancer-related psychological symptoms.  Results: Only the fatigue symptom in cancer patients was significantly correlated with all items of the EORTC QLQ-C30, whereas pain was correlated with a relatively small number (five items) of EORTC QLQ-C30 items compared to other psychological symptoms. Additionally, there were moderate to strong correlations between cancer-related pain, fatigue, anxiety, depression and poor sleep quality.  Conclusion: Cancer-related psychological symptoms were interrelated, and these symptoms were related to the multidimensional components of QoL. Fatigue was the most important factor influencing the overall QoL. We suggest that healthcare professionals consider a comprehensive approach to improving the QoL of patients with cancer.